Integrated electrospinning and electrospraying for tailoring composite membranes of nanofibers and microbeads for membrane distillation - Michaela Olisha S. Lobregas; Ratthapol Rangkupan; Hsiu-Po Kuo; Chalida Klaysom (Scientific Reports)
Abstract Membrane distillation (MD) is an emerging membrane-based thermal desalination technology for desalination. However, designing highly efficient MD membranes faces complication between large pore size for high flux and reduced pore size for excellent anti-wetting property. In this work, a unique composite nanofibrous membrane was developed using a simultaneous electrospinning and electrospraying technique. The membrane consisted of electrospun PVDF nanofibers and electrosprayed fluorinated TiO2-PVDF microclusters. The simultaneous dual-nozzle fabrication created an intertwined network of nanofibers and microclusters, resulting in a highly porous membrane structure with enhanced flux. The microclusters contributed to increased surface roughness and reduced surface energy, providing excellent liquid entry pressure and wetting resistance. The membrane achieved a flux of 22.5 kg m-2 h-1 and a salt rejection factor (SRF) of 0.999 for 24 h of MD operation with 3.5% NaCl. Additionally, it demonstrated good performance against surfactant-contaminated saline feed, maintaining a flux of 14.8 kg m-2 h-1 and SRF of 0.999. Compared to a conventional nanofibrous membrane, the composite membrane exhibited up to 55% increase in flux, highlighting its performance advantage. This work introduces a simple, scalable, and time-efficient fabrication strategy for producing high-performance MD membranes and offers valuable insights into membrane design for water desalination applications.